Teaching 'work' as the measure of work - NIKOS KANDERAKIS; ELENI DANILI (Metaichmio Publications, 2014)
This article describes a teaching approach to the concept of 'work' for the upper secondary Greek school students. The teaching material presented aims at (a) teaching 'work' as a measure of work, and (b) clarifying when (under what conditions) 'work' is produced. The design of the teaching activities has been inspired by the history of mechanics and guided by the studies and the arguments of the 19th century's engineers who created the magnitude of 'work' in an attempt to measure the quantity of work produced by motor engines, humans and animals. The activities include inquiries and experiments (or rather experiences), where students estimate quantitatively the work done by various acting agents in different circumstances. Students first study the cases of the vertical elevation of various weights by a human and then explore cases of other kinds of movements (e.g. a horizontal displacement of a weight) or other acting agents (e.g. motor engines). At the end, there is a metacognition discussion.